The Impact of COVID-19 Outbreak on Emotional and Cognitive Vulnerability in Iranian Women With Breast Cancer - Choobin, Mohammad H.; Mirabolfathi, Vida; Chapman, Bethany; Moradi, Ali Reza; Grunfeld, Elizabeth A.; Derakshan, Nazanin (Frontiers in Psychology, 2021)
The psychological cost on emotional well-being due to the collateral damage brought about by COVID-19 in accessing oncological services for breast cancer diagnosis and treatment has been documented by recent studies in the UK. The current study set out to examine the effect of delays to scheduled oncology services on emotional and cognitive vulnerability in women with a breast cancer diagnosis in Iran, one of the very first countries to be heavily impacted by COVID-19. One hundred thirty-nine women with a diagnosis of primary breast cancer answered a series of online questionnaires to assess the current state of rumination, worry, and cognitive vulnerability as well as the emotional impact of COVID-19 on their mental health. Results indicated that experienced delays on accessing oncology services significantly increased COVID related emotional vulnerability. Regression analyses revealed that after controlling for the effects of sociodemographic and clinical variables, women’s COVID related emotional vulnerability explained higher levels of ruminative response and chronic worry as well as poorer cognitive function. This study is the first in Iran to demonstrate that the effects of COVID-19 on emotional health amongst women affected by breast cancer can exaggerate anxiety and depressive related symptoms increasing risks for clinical levels of these disorders. Our findings call for an urgent need to address these risks using targeted interventions exercising resilience.